Estimation of Cohort Fertility Using Parity Progression Ratio - Shakya, Dhanendra Veer (Curriculum Development Journal, 2020)
This study attempts to analyze the levels and patterns of cohort fertility in Nepal in 2016 using data on parity progression ratios (PPRs). Simple PPRs, rather than synthetic PPRs or birth history of women, are used in this study from distribution of women by age and children ever born. Data on PPRs are used from 2016 Nepal Demographic and Health Survey to estimate cohort fertility of currently married and all women separately. Fertility is analyzed for different birth cohorts of women, specifically for birth cohorts of age groups 45-49, 20-24, 25-29, and 30-34 years, beside overall span of reproductive ages (15-49) for different purposes. The PPRs data are employed in this study in three different ways such as PPRs itself, proportion of women with at least ‘N’ number of children ever born (CEB), and cohort fertility rates. All three measures are implied to estimate cohort fertility of both currently married and all women separately. Fertility patterns are almost similar in all the three methods and other the measures show that the level of cohort fertility is still a little higher in Nepal, although it is declining gradually over time. The completed cohort fertility is estimated at around 4 in Nepal in 2016. The contribution of this article will be to check fertility level by applying this simple, but less common, method in estimating cohort fertility.